Epithelioid Sarcoma: A Case Report - Jain, Pooja; Kudwa, Ranjini (Annals of Pathology and Laboratory Medicine, 2020)
Epithelioid sarcoma is a rare highly aggressive soft tissue sarcoma with a high incidence of local recurrence and metastasis. It is a tumor of uncertain histogenesis & poses a diagnostic difficulty as it is often misdiagnosed as other benign or malignant condition. We present the case of 49-year-old male presenting with chief complaints of pain and gradually progressive swelling on right 3rd toe since 3 months. Based on clinicoradiological evaluation suggestive of malignancy, an amputation of toe was done. Histopathological & Immunohistochemical findings suggestive of Epithelioid sarcoma. The patient was referred to the oncology centre for further management where he was advised wide excision followed by radiotherapy. No regional or distant metastasis was found.